IMPLEMENTASI TEORI KOMUNIKASI SOSIAL BUDAYA DALAM PEMBANGUNAN INTEGRASI BANGSA - Aw, Suranto (Informasi, 2015)
AbstractDevelopment is a process that is carried out continuously in a region over time. Development leads the improvement of the lives and well-being, both in terms of material and nonmaterial. To Indonesia, the development process is a planned activity to achieve national goals as mandated in the 1945 Constitution, which among others, to promote the general welfare, united, sovereign, fair, and prosperous. Indicators of well-being are not just limited to the economic aspect and materialistic, but also concerning aspects of harmony, unity, and integration of national life in dignity characterized by solidarity excellence. So that it is needed to consider the implementation of the theories of social and cultural communication in the development process.AbstrakPembangunan adalah suatu proses yang dilakukan secara terus menerus pada suatu wilayah dari waktu ke waktu. Pembangunan bermuara para peningkatan kehidupan dan kesejahteraan, baik dari sisi material maupun nonmaterial. Bagi Bangsa Indonesia, proses pembangunan adalah aktivitas terencana untuk mencapai tujuan nasional sebagaimana diamanatkan dalam Pembukaan UUD 1945, yaitu antara lain untuk memajukan kesejahteraan umum, bersatu, berdaulat, adil, dan makmur. Indikator kesejahteraan tidak hanya terbatas pada aspek ekonomis dan materialistis, melainkan juga menyangkut aspek keharmonisan, kebersamaan, dan integrasi hidup berbangsa secara bermartabat yang ditandai oleh adanya solidaritas yang prima. Berkenaan dengan itu, perlu dipertimbangkan implementasi teori-teori komunikasi sosial budaya dalam proses pembangunan.Keywords: Socio-Cultural Communication, Growth, Integration